Identification of Bacillus cereus and Cronobacter sakazakii on food products consumed by infants and children in Bangladesh - Medha, Maysha Mahjabeen Hassan; Siraj, Suraya; Hossain, Fariya (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.